Sustainable Shared Mobility: Current Status and Future Prospects - Turoń, Katarzyna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a comprehensive compilation of research on new urban mobility. It contains proprietary, current studies on shared mobility, such as car sharing or scooter sharing in relation to commercial use as part of short-term rental systems or for use by postal services. In addition, it broadly refers to the subject of bicycles and bike-sharing systems. It includes research on professional e-bikes with parameters such as velocity, cadence and power data as well as research on measuring the intensity of bicycle traffic, which can be used to evaluate and improve bike-sharing systems. The reprint provides a valuable resource for researchers, practitioners, and policymakers who are interested in the challenges and opportunities associated with the development of new mobility solutions.